Women’s land rights in Africa - Ghebru, Hosaena (International Food Policy Research Institute, 2019)
2019 ReSAKSS Annual Trends and Outlook Report 45 Anew wave of land reforms has swept across a large number of developing countries since the millennium. Prior to the millennium, land tenure reform toward an individual freehold system was seen as a prerequisite for development in Africa south of the Sahara (SSA) by governments, development partners, and practitioners (Feder and Noronha 1987; Migot- Adholla et al. 1994). The arguments in favor of reforming the customary African land tenure system were mainly based on the neoclassical economic theory of property rights (Demsetz 1967; Barzel 1997) that predicts greater productivity as land tenure becomes more secure and individualized. Reflecting neoliberal thinking about private property rights, Besley (1995) identified three channels through which secure property rights can, in principle, bring about positive economic outcomes, namely (1) tenure security and higher land investment incentives; (2) smooth functioning of the land markets (tradability) that smooths farm input adjustment; and (3) facilitating access to institutional credit by allowing land to be used as collateral. These hypothesized effects of tenure security rely heavily on the neoclassical framework that presupposes markets for all goods and services (including credit and insurance markets) exist and, therefore, market clearing prices determine demand and supply choices of households (Bardhan 1989; Hoff, Braverman, and Stiglitz 1993).